Effects of a nanocomposite containing Orbignya speciosa lipophilic extract on Benign Prostatic Hyperplasia - Boylan, Fabio (My University, 2011)
Aim of the study : Lower urinary tract symptoms (LUTS) are a common complaint among aging men and are usually caused by Benign Prostatic Hyperplasia (BPH). A number of medical treatments for LUTS/BPH exist, such as ?-blockers, 5 ?-reductase inhibitors, phytotherapeutical drugs and combination therapies. Babassu is the common name of a Brazilian native palm tree called Orbignya speciosa, whose kernels are commonly used (eaten entirely or as a grounded powder), in parts of Brazil for the treatment of urinary disorders. This study investigates the effects of Orbignya speciosa nanoparticle extract, a newly developed phytotherapic formulation derived from the kernels of babassu, in the treatment of BPH. Materials and Methods : Orbignya speciosa extract was obtained from the kernels, a nanoparticulate system was developed and acute toxicity test was performed. BPH primary stromal cell and tissue cultures were established and treated with 300 ?g/mL Orbignya speciosa nanoparticle (NanoOse) extract in order to evaluate its effects on apoptosis induction, cytotoxicity, cell morphology and proliferation. Results : Our results indicated that NanoOSE shows no toxicity in animals and acts incisively by promoting morphological cell changes, reducing cell proliferation as well as inducing necrosis/apoptosis on BPH cells and tissues. Conclusions : This study provided the first report of the successful use of NanoOSE on BPH treatment which corroborates with the popular use of the kernels of this plant. The results also suggest the potential of NanoOSE as a candidate new phytotherapeutic agent on the management of BPH.
PUBLISHED
Keywords: Urology; Benign Prostatic Hyperplasia; Orbignya speciosa extract; Cancer; International Development